Successful treatment of relapsing autoimmune pancreatitis in primary Sjögren's syndrome with Rituximab: Report of a case and review of the literature (2009)
Autoimmune pancreatitis (AIP) is a rare disorder often associated with multiple autoimmune diseases like rheumatoid arthritis, inflammatory bowel disease and Sjögren’s syndrome (SS). Although knowledge of AIP has grown over the last few years, little is certain about its cause and pathogenesis. Positive immunologic markers like antinuclear antibodies (ANA) or elevated serum levels of IgG4, systemic autoimmune disease association and positive response to oral steroid therapy strongly supports the idea of autoimmune mechanisms involved in the pathogenesis of AIP. We describe the first case reported on the literature of a patient with primary SS who developed relapsing AIP to steroids but responded successfully to Rituximab (RTX) therapy. New theories about the role of B-cells activity in SS and other autoimmune diseases has encourage the use of RTX, proving tolerance and efficacy especially in extra-glandular manifestations.